Frontispiece: Synthesis and Chiroptical Properties of Chiral Carbazole‐Based BODIPYs. Issue 19 (1st April 2020) - Maeda, Chihiro; Suka, Keita; Nagahata, Keiji; Takaishi, Kazuto; Ema, Tadashi
Abstract : Chiral BODIPY derivatives and congeners have been recognized as promising circularly polarized luminescence (CPL) dyes. The synthesis of chiral carbazole‐based BODIPYs with binaphthyl units through the Et2 AlCl‐mediated reaction is described. The substituent effects on the chiroptical properties were investigated by experimental studies and DFT calculations. These chiral BODIPY congeners showed CPL both in solution and in the solid state with | g lum | values up to 3.8×10 −3 in the visible to NIR region. Find out more in the Full Paper by C. Maeda, T. Ema et al. on page 4261 ff.